Periplasmic form of dipeptidyl aminopeptidase IV from Pseudoxanthomonas mexicana WO24: purification, kinetic characterization, crystallization and X‐ray crystallographic analysis. Issue 11 (2nd November 2017) - Roppongi, Saori; Tateoka, Chika; Fujimoto, Mayu; Iizuka, Ippei; Morisawa, Saori; Nakamura, Akihiro; Honma, Nobuyuki; Suzuki, Yoshiyuki; Shida, Yosuke; Ogasawara, Wataru; Tanaka, Nobutada; Sakamoto, Yasumitsu; et al.
Abstract : The periplasmic form of dipeptidyl aminopeptidase IV from P. mexicana WO24 was crystallized in complex with the tripeptide Lys‐Pro‐Tyr. X‐ray diffraction data were collected to 1.90 Å resolution. Abstract : Dipeptidyl aminopeptidase IV (DAP IV or DPP IV) from Pseudoxanthomonas mexicana WO24 (PmDAP IV) preferentially cleaves substrate peptides with Pro or Ala at the P1 position [NH2 ‐P2‐P1(Pro/Ala)‐P1′‐P2′…]. For crystallographic studies, the periplasmic form of PmDAP IV was overproduced in Escherichia coli, purified and crystallized in complex with the tripeptide Lys‐Pro‐Tyr using the hanging‐drop vapour‐diffusion method. Kinetic parameters of the purified enzyme against a synthetic substrate were also determined. X‐ray diffraction data to 1.90 Å resolution were collected from a triclinic crystal form belonging to space group P 1, with unit‐cell parameters a = 88.66, b = 104.49, c = 112.84 Å, α = 67.42, β = 68.83, γ = 65.46°. Initial phases were determined by the molecular‐replacement method using Stenotrophomonas maltophilia DPP IV (PDB entry2ecf ) as a template and refinement of the structure is in progress.